Heavy metal content and element analysis of infant formula and milk powder samples purchased on the Tanzanian market: International branded versus black market products. (30th July 2018) - Sager, M.; McCulloch, C.R.; Schoder, D.
Highlights: Heavy metal content and analysis of 43 elements of infant formula were measured. 43 milk powder samples from the East African market were analyzed using ICP-MS. Results for East African milk powders were compared to Austrian reference samples for toxic and essential trace elements. 2.3% of East African milk powders were contaminated with lead (240 µg/kg dry weight). Abstract: Milk powder is a food for malnourished African children and for healthy infants of women with HIV/AIDS. High demand and low purchasing power has resulted in a huge informal, black market in Sub-Saharan Africa. Forty-three milk powder batches were analyzed for 43 chemical elements using ICP-MS One sample (2.3%) was contaminated at a lead concentration of 240 µg/kg dry weight exceeding the European threshold (130 µg/kg dry weight). Macroelement contents revealed a trend decreasing in concentration through skimmed, full cream products to infant formulae. Concentration ranges by dry weight differed in respect of uncertainty intervals of  ±10%. Median Ca, K and P concentrations declined from 11.14 g/kg to 3.21 g/kg, 14.11 g/kg to 4.95 g/kg and 9.12 g/kg to 2.75 g/kg dry mass, respectively. Milk powder samples obtained from the Tanzanian black market were comparable in respect of nutritional and chemical content to international branded full cream products.